Chinese Herbal Formula (CHF03) Attenuates Non-Alcoholic Fatty Liver Disease (NAFLD) Through Inhibiting Lipogenesis and Anti-Oxidation Mechanisms - Cui, Yizhe; Chang, Renxu; Zhang, Tao; Zhou, Xiaocui; Wang, Qiuju; Gao, Haiyun; Hou, Lintong; Loor, Juan J.; Xu, Chuang (Frontiers in Pharmacology, 2019)
Nonalcoholic fatty liver disease (NAFLD) is a hepatic ailment with a rapidly increasing incidence in the human population due largely to dietary hyper nutrition and subsequent obesity. Discovering effective natural compounds and herbs against NAFLD can provide alternative and complementary medical treatments to current chemical pharmaceuticals. In this study, ICR male mice were fed a high-fat diet (HFD) in vivo and the AML12 cells were treated with palmitic acid (PA) in vitro. We explore the protective effect and potential mechanism of Chinese Herbal Formula (CHF03) against NAFLD by HE staining, transmission Electron Microscopy assay, Western blotting, and gene expression. In vivo, oxidative stress markers (GSH, GSH-px, MDA, SOD, and CAT) confirmed that CHF03 alleviated oxidative stress and abundance of NF-κB proteins indicating a reduction in inflammation and oxidative stress. The lower protein abundance of ACACA and FASN indicated a preventive effect on lipogenesis. Histological and ultrastructural observations revealed that CHF03 inhibited NAFLD. Expression of Srebf1, Fasn, and Acaca, which are associated with lipogenesis, were downregulated. In vitro, genes and proteins are expressed in a dose-dependent manner, consistent with those in the liver. CHF03 inhibited lipid accumulation and expression of NF-κB, nuclear transfer, and transcriptional activity in AML12 cells. The CHF03 might have a beneficial role in the prevention of hepatic steatosis by altering the expression of lipogenic genes and attenuating oxidative stress.